AKTIVITAS ANTICAPLAK SEDIAAN SPRAY YANG MENGANDUNG MINYAK ROSEMARY,BERGAMOT DAN CUKA APEL - Ath-Thaariq, Affan Aufar; Prasetyo, Bayu Febram; Supriyono (Jurnal Buana Farma, 2025)
Apple cider vinegar and rosemary oil have an acaricidal effect on R. sanguineus ticks. Both ingredients offer health benefits. This study aimed to observe the effect of a spray preparation containing apple cider vinegar and rosemary oil at various concentrations on the mortality of R. sanguineus ticks. The study was conducted from February 2025 to April 2025. It used 75 R. sanguineus ticks, divided into 5 groups, with each group having three repetitions. K1, the negative control, was treated with pure distilled water. K2, the positive control, was treated with Fipronil 3% (Frontline brand). K3 was given bergamot oil 5%, rosemary oil 10%, and apple cider vinegar 5%. K4 was given bergamot oil 5%, rosemary oil 10%, and apple cider vinegar 10%. K5 was given bergamot oil 5%, rosemary oil 10%, and apple cider vinegar 15%. Each treatment group consisted of 5 ticks. Observations were made at 30, 60, 90, 120, and 180 minutes post-contact. The results showed that the group treated with bergamot oil 5%, rosemary oil 10%, and apple cider vinegar 15% achieved a Lethal Time 50 (LT50) at 106 minutes. The conclusion indicates that apple cider vinegar at a concentration of 15% required the least amount of time to kill the ticks